Три принца: роман; [пер. с англ.] / Джойс Данвилл - Данвилл Джойс (Алая Роза, 1995)
Экземпляры: ф.15 (20131115) / Инвентарный номер: 44713 / Цена: 35.00 / Авт.знак: Д 17 / ГРНТИ: 17.82 / ББК: 84(7Сое)